Does Sleep Quality affect The Occurrence and Detection of Subclinical Arrhythmiasin Young Adults when Measured using Wearable ECG Devices? : A Systematic Review - Erlin Prawita Sari; M Ramazali; Gita Noor Azizah; Aan Try Maryani (The Indonesian Journal of General Medicine, 2026)
Introduction: Poor sleep quality is prevalent among young adults (18–39 years) and is linked to adverse cardiovascular outcomes. Wearable ECG devices offer a novel opportunity to assess both sleep and subclinical arrhythmias in real-world settings. However, the direct relationship between sleep quality and subclinical arrhythmia occurrence in healthy young adults remains unclear. This systematic review evaluates whether sleep quality affects the occurrence and detection of subclinical arrhythmias in young adults using wearable ECG devices. Methods: A systematic screening of literature was performed based on predefined criteria: population (young adults 18–39 years), sleep quality measurement (validated instruments), ECG technology (wearable devices), arrhythmia type (subclinical/asymptomatic), temporal linkage (concurrent sleep and ECG recording), and absence of cardiovascular disease, arrhythmogenic medications, shift work, or diagnosed sleep disorders. Results: From a large pool, multiple studies demonstrated that poor sleep quality (short duration, fragmentation, irregularity, deprivation) consistently shifted autonomic cardiac regulation toward sympathetic dominance and reduced parasympathetic (vagal) tone, as indexed by heart rate variability (HRV). For example, after 48-hour sleep deprivation, the LF/HF ratio increased significantly (3.02 vs. 2.48, p<0.001) (3). Sleep restriction to 4 hours/night for 5 nights increased resting heart rate from 60 to 63 bpm and LF/HF from 4.6 to 6.0 (1). Sleep irregularity reduction from 57 to 31 minutes improved resting heart rate (65 to 62 bpm, p=0.005) and increased RMSSD (34 to 42 ms, p=0.009) (2). In young adults with circadian disruption, sleeping <6 hours increased ventricular ectopic events (12). Epidemiological data showed frequent nighttime awakening was associated with a 33% increased risk of atrial fibrillation (HR 1.33, 95% CI 1.17–1.51, p<0.001) (6). Wearable devices achieved 85–95% sensitivity for AF detection (8), and the Zio patch showed 88.8% sensitivity for sleep detection versus polysomnography (10). Discussion: The evidence robustly supports that poor sleep quality impairs autonomic cardiac regulation in young adults via sympathetic activation and vagal withdrawal. This autonomic shift is a known arrhythmogenic substrate. Wearable technologies are now capable of simultaneously monitoring sleep quality and detecting subclinical arrhythmias. The critical remaining gap is the direct demonstration that sleep quality variation modulates the frequency, timing, or detectability of subclinical arrhythmic events in naturalistic settings. Conclusion: Poor sleep quality significantly alters autonomic cardiac function in young adults toward a pro-arrhythmic state. Wearable ECG devices are technically capable of assessing both parameters. Future purpose-designed studies combining longitudinal wearable cardiac monitoring with validated sleep assessment in young adult cohorts are needed to directly link sleep quality to subclinical arrhythmia detection.